PENGARUH TEKANAN VACUUM CONDENSER TERHADAP KINERJA STEAM TURBINE GENERATOR - Hidayatullah, Nasrul; Wahyudi, Dedi; Nuramal, Agus (UNIB Press, 2023)
Condenser is an main equipment on power steam electricity system generator. Condenser is an head exchanger that functions as a phase changer from the steam turbine output into water, which is where water results condensation the will pumped to HRSG for used back. Vacuum condenser working for speed up the condensation process in the condenser. PT. PLN (Persero) UPDK keramasan is generator electricity consists of 2 units from gas and steam power plant with power by gas turbine generator of ± 27 MW and a steam turbine generator of ± 13 MW so that the total each unit is 40 MW. This research to determine of effect vaccum condenser pressure of condenser with power turbine, and efficiency thermal. calculation obtained at a vacuum condenser pressure of 15,41 kPa at a turbine power was 9681 kW, and obtain efficiency thermal was 20,39%. On pressure vacuum condenser 15,09 kPa at a turbine power was 9602 kW, and obtain efficiency thermal was 20,24%.